The Resistance Measurement Method of the Conducting Textiles - Lipol, Lefayet Sultan; Islam, Mayedul; Sultana, Nazrima (European Scientific Journal, ESJ, 2016)
The report describes the technique to measure the resistance of some novel conducting threads. All of the measurements were performed in the EMC lab at SP Technical Research Institute of Sweden, Boras. The conducting threads were received from Ms. Azadeh Soroudi of the University of Boras. The conducting additive used for the threads was Carbon Black. The resistance was measured using two different methods: The two-terminal measurement method and the four-terminal measurement method. A result from the comparison of the two methods was that the two terminal measurement method provided more information than the fourterminal method. There seemed to be no advantage to use the four terminal method at all, for the resistance range studied.